Multiple Primary Cancers Associated with Merkel Cell Carcinoma in Queensland, Australia, 1982–2011 - Youlden, D.; Youl, P.; Soyer, H.; Fritschi, Lin; Baade, P. (Blackwell Science, 2014)
The relatively high incidence of Merkel cell carcinoma (MCC) in Queensland provides a valuable opportunity to examine links with other cancers. A retrospective cohort study was performed using data from the Queensland Cancer Registry. Standardized incidence ratios (SIRs) were used to approximate the relative risk of being diagnosed with another primary cancer either following or prior to MCC. Patients with an eligible first primary MCC (n=787) had more than double the expected number of subsequent primary cancers (SIR=2.19, 95% confidence interval (CI)=1.84–2.60; P<0.001). Conversely, people who were initially diagnosed with cancers other than MCC were about two and a half times more likely to have a subsequent primary MCC (n=244) compared with the general population (SIR=2.69, 95% CI=2.36–3.05; P<0.001). Significantly increased bi-directional relative risks were found for melanoma, lip cancer, head and neck cancer, lung cancer, myelodysplastic diseases, and cancer with unknown primary site. In addition, risks were elevated for female breast cancer and kidney cancer following a first primary MCC, and for subsequent MCCs following first primary colorectal cancer, prostate cancer, non-Hodgkin lymphoma, or lymphoid leukemia. These results suggest that several shared pathways are likely for MCC and other cancers, including immunosuppression, UV radiation, and genetics.